Guidelines in the experimental validation of a 3D heat and fluid flow model of keyhole laser welding. (16th March 2016) - Courtois, Mickael; Carin, Muriel; Le Masson, Philippe; Gaied, Sadok; Balabane, Mikhaël
Abstract: During the past few years, numerous sophisticated models have been proposed to predict in a self-consistent way the dynamics of the keyhole, together with the melt pool and vapor jet. However, these models are only partially compared to experimental data, so the reliability of these models is questionable. The present paper aims to propose a more complete experimental set-up in order to validate the most relevant results calculated by these models. A complete heat transfer and fluid flow three-dimensional (3D) model is first proposed in order to describe laser welding in keyhole regimes. The interface is tracked with a level set method and fluid flows are calculated in liquid and gas. The mechanisms of recoil pressure and keyhole creation are highlighted in a fusion line configuration chosen as a reference. Moreover, a complete validation of the model is proposed with guidelines on the variables to observe. Numerous comparisons with dedicated experiments (thermocouples, pyrometry, high-speed camera) are proposed to estimate the validity of the model. In addition to traditional geometric measurements, the main variables calculated, temperatures, and velocities in the melt pool are at the center of this work. The goal is to propose a reference validation for complex 3D models proposed over the last few years.